Nuclear localization of basonuclin in human keratinocytes and the role of phosphorylation - Iuchi, Shiro (The National Academy of Sciences of the USA, 1997)
Basonuclin is a zinc-finger protein found in basal cells of the epidermis. In human keratinocyte cultures, basonuclin is susceptible to serine-phosphorylation and the addition of the phosphatase inhibitor, okadaic acid, promotes accumulation of basonuclin in the cytoplasm. The region of basonuclin containing the nuclear localization signal of basonuclin is necessary for nuclear localization of the protein and Ser-541, located immediately C-terminal to the nuclear localization signal, is the principal phosphorylation site in vitro. A nearly complete basonuclin transiently expressed in cultured keratinocytes localizes predominantly in the nucleus, but substitution of aspartic acid for Ser-541 promotes cytoplasmic localization. The same substitution of Ser-537 has a similar but weaker effect. Substitution of both serine residues by alanine leads to nuclear localization. These results show that nuclear localization of basonuclin depends on serine dephosphorylation, primarily of Ser-541. Different subcellular locations of basonuclin in different keratinocyte subtypes are therefore most likely to be controlled by the state of phosphorylation of Ser-541.